Research on the failure mechanism of elastic strip fracture in corrugated sections of metros. (January 2023) - Cui, Xiaolu; Bao, Pengyu; Li, Tong; Qi, Wei
Highlights: The failure mechanism of clip fracture is studied by resonance response and fatigue failure. A wheelset-rail-fastener system in corrugated section is built. The friction-coupled vibration of the whole system is the key cause of fastener clip fracture. Fastener clip failure can be controlled below 0.078 mm by grinding. Abstract: Rail corrugation is a common problem of railway, where the failure of the fastener clip in the corrugated section is serious. According to field investigations, a complete finite element model of the wheelset-rail-fastener system and an irregularity surface of corrugated wear are constructed. Then, the failure mechanism of elastic strip fracture in the corrugated section is studied from the perspectives of the resonance response and the fatigue failure, respectively. Finally, the relevant treatment measure is proposed through the grinding treatment of rail corrugation. Results show that the frictional coupling vibration of the wheelset-rail-fastener system in the corrugated section may lead to the resonance and the failure of fastener clips. Besides, the vibration of the entire system is intensified by the corrugated wear, which reduces fatigue lives of fastener clips. Moreover, the fracture of elastic strips can be restrained by controlling the corrugated depth below 0.078 mm.